Małe i duże kino. Europejskie wizje - Janina Falkowska (Postscriptum Polonistyczne)
The article contrasts small european cinemas and large such as Hollywood cinema. The author discusses the issues of the international conference European Visions. Small Cinemas in Transition to be held at the University of Western Ontario in June 2010. The analysis of contemporary Polish productions leads to the conclusion about how vague the border is between naming a cinema “big” or “small”, “universal” or “local” and how relevant issues of national identity have become in recent years.